PENGARUH PRINSIP AL-MUZARA’AH DAN AL-MUKHABARAH TERHADAP PERJANJIAN BAGI HASIL TAMBAK GARAM DI DESA MARENGAN LAOK - Cahyati, Nur; Rohman, Abdur (Program Studi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Tarbiyatut Tholabah, 2022)
t: This research was conducted to examine how the role of the people of Marengan Laok Villagein producing salt for their welfare. If you look at Madura Island, the biggest potential for producing salt isin Sumenep Regency, namely in Kalianget District. Therefore, I took this research in Marengan LaokVillage, Kec. Kalianget to make research easier.This research is focused on the contract agreement made by the land owner (tambak) and the land worker(tambak). This study also uses qualitative methods by means of observation, documentation and directinterviews with the people in Marengan Laok Village. While the data analysis in this study usesdescriptive and introspective analysis of all forms of human consciousness and experience in terms of sensory,conceptual, moral, aesthetic, religious and economic aspects. In accordance with the stages of the target outputof this research is the Effect of the Principles of Al-Muzara'ah and Al-Mukhabarah on the Salt FarmProfit Sharing Agreement in Marengan Laok Village.Keywords: Salt, Al-Muzara'ah, Al-Mukhabarah